The association between cash flow variables and market risk on the Johannesburg Stock Exchange: An empirical analysis - Wessie J.A. Wessels; Johan du P. Smith; Wim R. Gevers (South African Journal of Business Management, 1993)
Cash flow from operations can be considered an important indicator of the quality of income of a company. The value of cash flow data was emphasized by Ismail Kim who found that cash-flow-based accounting betas have significant incremental explanatory power over earnings-based betas in explaining the variability in market risk. In this article similar research is reported which was conducted on a sample of companies extracted from the Industrial Section of the Johannesburg Stock Exchange and using the methodology proposed by Ismail Kim. A three year moving average smoothing procedure was also applied to the accounting return variables in order to reduce the effect of short-term influences on the cash flow. Although it was not possible from the research to obtain similar statistically significant results for the South African market (partly because of the relatively small sample size), it was found that the simple linear regression model based on the smoothed cash flow beta did provide significant explanatory power of the variability in market beta.
Keywords: 650